The Polemic of Charging Interest (Riba) Amoung Conventional Bank Employees - Nanang Bagus Setiawan; Aries Kurniawan; Ilham; Beni Dwi Komara; Nuzulul Fatimah; Tatag Herbayu Latukismo; Heri Cahyo Bagus Setiawan; Riyan Sisiawan Putra (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
This study aims to determine the polemic experienced by a number of conventional bank employees, who know and realize that bank interest is usury or who still believe that bank interest is not usury, because they are only employees who work in banking companies and do not practice usury individually. per individual. From the two attitudes of banking employees in responding to the bank interest usury mentioned above, the study will focus on employees who have the attitude that bank interest is usury, while those who have the opposite attitude are clearly not going to take action to resign from their office. After focusing on anti-anti rip banking employees, it was found that them there were several obstacles to resigning, the first obstacle was internal, namely the lack of support from the family, both the nuclear family and the extended family, while the second obstacle was the repayment of employee loans that they enjoyed before knowing. and realize that bank interest is charging interest or usury (riba). Of the two obstacles or resign constraints will lead to further attitudes for a number of these employees. The attitude of a number of employees who have not received family support, some continue to return to work in a professional manner and some work just to abort their obligations or in other words work not seriously because they are not in accordance with their conscience. While the attitudes of a number of employees who are still in debt are more varied in attitude, some of them continue to work as usual while waiting for the right moment to pay off their debts, some are still working even though half-heartedly while trying to find a way out so that their debts can be paid off. and some of them are unanimously determined to leave office immediately or borrow a term in the military world, namely by deserting or leaving work by temporarily leaving the debt unpaid, even though they plan to pay it off at a later date. This study used a qualitative research method, namely the collection of in-depth interview data with former employees and active banking employees. Researchers also conducted focus group discussions / FGDs (Forum Group Discussion) among bank employees who were anti-microbial but still active and former bank employees who had resigned. As a result, there are five attitudes of banking employees in facing the resignation polemic due to bank interest rates in Indonesia. First, employees return to work professionally because they still get salaries from banking companies. Second, employees work only to abort obligations because they are not in accordance with their conscience. Third, employees who are still in debt continue to work professionally while looking for a way to pay off their debts. Fourth, employees who work half-heartedly while looking for ways to pay off loans. Fifth, if their resignation application by leaving debt and willing to pay off in installments is refused by the office, they prefer to leave the company unilaterally or go out of business.